2013
DOI: 10.1038/ng.2835
|View full text |Cite
|
Sign up to set email alerts
|

Minke whale genome and aquatic adaptation in cetaceans

Abstract: The shift from terrestrial to aquatic life by whales was a substantial evolutionary event. Here we report the whole-genome sequencing and de novo assembly of the minke whale genome, as well as the whole-genome sequences of three minke whales, a fin whale, a bottlenose dolphin and a finless porpoise. Our comparative genomic analysis identified an expansion in the whale lineage of gene families associated with stress-responsive proteins and anaerobic metabolism, whereas gene families related to body hair and sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
266
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(281 citation statements)
references
References 70 publications
11
266
0
4
Order By: Relevance
“…Recent publications presenting whole-genome sequence analyses of whales lack information about the distribution of repetitive sequences in the genome. Routinely, all repetitive sequences are repeatmasked and avoided [Yim et al, 2014;Park et al, 2015]. In the present work, to gain deeper insight into the organization of heterochromatin in toothed and baleen whales, we mapped telomeric repeat, ribosomal DNA, common component, and heavy satellite in the metaphase chromosomes of the gray whale and the pilot whale.…”
mentioning
confidence: 99%
“…Recent publications presenting whole-genome sequence analyses of whales lack information about the distribution of repetitive sequences in the genome. Routinely, all repetitive sequences are repeatmasked and avoided [Yim et al, 2014;Park et al, 2015]. In the present work, to gain deeper insight into the organization of heterochromatin in toothed and baleen whales, we mapped telomeric repeat, ribosomal DNA, common component, and heavy satellite in the metaphase chromosomes of the gray whale and the pilot whale.…”
mentioning
confidence: 99%
“…Baleen whales lack the dorsal domain of the olfactory bulb [Kishida et al, 2015b], and the olfactory bulb is absent in toothed whales [Oelschläger et al, 2010]. Artiodactyls express thousands of OR and some V1R (cows, 40 intact genes), but not functional V2R [Shi and Zhang, 2007], whereas cetaceans possess about 60 OR and very few V1R genes (mink whales, two intact genes; bottlenose dolphins, one gene) and lack V2R [Yim et al, 2014;Kishida et al, 2015a]. Unlike in cetaceans, a pair of large olfactory bulbs [Garrod, 1880;Butti et al, 2014] and peripheral vomeronasal organs [Estes, 1991;pers.…”
mentioning
confidence: 99%
“…Several studies have recently reported that AQP2 was positively selected for during the secondary adaptation in cetacean species, suggesting that the evolution of the gene was an important event in the development of enhanced capacity for water reabsorption in the renal tubules (Nery et al, 2013;Xu et al, 2013;Yim et al, 2014). Extensive information can be obtained from genome-scale analyses, providing insight into the nature and extent of selective pressures that contributed to the evolution of a particular group.…”
Section: Discussionmentioning
confidence: 99%
“…For these characteristics of AQP2 and in view of reports that AQP2 was positively selected during the secondary adaptation of cetacean species to the marine environment (Nery et al, 2013;Xu et al, 2013;Yim et al, 2014), for this study it was hypothesized that AQP2 could play some roles in cellular osmoregulation in cetaceans, who are living in a hypertonic environment in comparison to their body fluids. It was previously reported that AQP2 is distributed in the principal cells of the kidneys of the bottlenose dolphin and Baird's beaked whale, similar to terrestrial mammals (Suzuki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%